Biogenic carbonate mercury and marine temperature records reveal global influence of Late Cretaceous Deccan Traps - Meyer, Kyle W.; Petersen, Sierra V.; Lohmann, Kyger C; Blum, Joel D.; Washburn, Spencer J.; Johnson, Marcus W.; Gleason, James D.; Kurz, Aaron Y.; Winkelstern, Ian Z. (Nature communications, 2019)
The climate and environmental significance of the Deccan Traps large igneous province of west-central India has been the subject of debate in paleontological communities. Nearly one million years of semi-continuous Deccan eruptive activity spanned the Cretaceous-Paleogene boundary, which is renowned for the extinction of most dinosaur groups. Whereas the Chicxulub impactor is acknowledged as the principal cause of these extinctions, the Deccan Traps eruptions are believed to have contributed to extinction patterns and/or enhanced ecological pressures on biota during this interval of geologic time. We present the first coupled records of biogenic carbonate clumped isotope paleothermometry and mercury concentrations as measured from a broad geographic distribution of marine mollusk fossils. These fossils preserve evidence of simultaneous increases in coastal marine temperatures and mercury concentrations at a global scale, which appear attributable to volcanic CO 2 and mercury emissions. These early findings warrant further investigation with additional records of combined Late Cretaceous temperatures and mercury concentrations of biogenic carbonate. The relative role of the Deccan Traps volcanic activity versus the role of the Chicxulub impact event in terms of potential contributions to the Cretaceous-Paleogene (K-Pg) mass extinction has been subject to longstanding debate. Here, the authors observe a global signal of abruptly increased ocean temperatures and elevated [Hg] in the same biogenic carbonate specimens, prior to the impact event but aligning with the onset of Deccan volcanism.